RESEARCH OF METHODS TO CREATE A PSYCHOLOGICAL ENVIRONMENT IN FOREIGN LANGUAGE TEACHING - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
Each lesson and each of its elements has its meaning, methodical psychological aspects, psychological aspects of the most effective techniques and methods, reasonable requirements, a working atmosphere, and favorable conditions of communication, which will make students smile, laugh, positive emotions, and ultimately serve the Improving the psychological climate in the classroom.